O uso de artefatos históricos na educação de jovens e adultos - Silva, Viviane Sousa da (2018)
This work aimed to investigate the contribution of the use of historical artifacts in the Education of Young and Adults, through structured activities. To this end, we set out specific objectives: Elaborate a proposal of structured activities that use historical artifacts; To develop the proposal of activities in the Education of Youths and Adults; To evaluate the potentialities and limitations of the proposal of structured activities that se historical artifacts in the Education of Youths and Adults. In order to base this work, we are based on the National Curricular Parameters (BRASIL, 1998) and authors like D'Ambrósio (1999), referring to the conceptions and perspectives of the History of Mathematics; Fonseca (2012), with regard to Mathematics Education for Young People and Adults; Mendes (2001), with regard to historical activities, Oliveira (2009), regarding the Use of Historical Artifacts in Mathematics. It was an exploratory qualitative research, carried out with 25 students, of the EJA High School, of a State Public School of Mamanguape Municipality, Paraíba. As a result we find that it is possible to work with the historical artifacts in the EJA, since the teacher makes a plan of how these activities will be developed in the classroom; that in EJA there is still a great lack of mathematical learning; that despite the difficulties presented by the students, the classes were very productive and the students very participative, always talking with colleagues about the activities worked in the classroom. We conclude that the use of historical artifacts can contribute to the student's process and learning, allowing the subject to interact and exchange ideas with the teacher and his colleagues, thus making classes more productive and dynamic.